Mathematical modeling of catalytic reactor for oxidizing phosphorus containing gases - Meruert, Akzhigitova; Sharip, Yeskendirov; Zhanat, Umarova; Othman, Mohamed (AIP Publishing LLC, 2013)
In this article has been suggested an approach to reactor modeling of phosphine oxidation with account of phase distribution in the volume of catalyst, based on the theoretical developments of work. This method allows working out a method of calculation of devices efficiency for phosphine oxidation with account of phase distribution in the volume of the device.